2017
DOI: 10.1111/jpn.12629
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lactobacillus isolates on growth performance, immune response, intestinal bacterial community composition of growing Rex Rabbits

Abstract: The objective of this experiment was to investigate the effect of Lactobacillus isolates on intestinal bacterial community composition of growing Rex Rabbits. A total of 120 weaned Rex Rabbits (30 days old, 30 per group) were used for the experiment, which started after an adaptation period of 7 days. The control group was fed with basal diet only, while the treatment I, II and III groups were fed with basal diet adding antibiotics, Lactobacillus zeae (LB1) and Lactobacillus casei (L3) respectively. Growth per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 43 publications
5
20
0
Order By: Relevance
“…The TP values observed in the current trial were lower than the normal ranges for rabbits (Melillo, 2007;Wang et al, 2017). They were, conversely, within the range reported by Özkan et al (2012).…”
Section: Serum Biochemical Parameterssupporting
confidence: 89%
See 2 more Smart Citations
“…The TP values observed in the current trial were lower than the normal ranges for rabbits (Melillo, 2007;Wang et al, 2017). They were, conversely, within the range reported by Özkan et al (2012).…”
Section: Serum Biochemical Parameterssupporting
confidence: 89%
“…The GLU values observed in the current trial were within the normal ranges for rabbits (Melillo, ; Özkan et al., ; Wang, Zhu, Li, & Huang, ). Glucose was, however, lower than that reported by Igwebuike et al.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Meanwhile, the Clostridium count was not affected. Wang et al [32]conclued that Lactobacillus isolates LB1 and L3 can alter the gut microbiota to the direction of more abundance and diversity, particularly in the cecum,by pyrosequencing-based analysis .Simonova et al [30]performed a similar study whereby E. faecium CCM7420 was administrated as a probiotic in rabbits for 21 and 42 days and reported that the probiotic increased the counts of Enterococci but was unable to modulate the levels of other faecal bacteria such as Staphylococci and Staphylococcus aureus.…”
Section: Effects Of Probiotics On Intestinal Microflora In Rabbitsmentioning
confidence: 99%
“…Wang et al [35]found that Firmicutes, Bacteroidetes, Proteobacteria, and Verrucomicrobia (90.5%-97.7%) played an important role in the cecum, duodenum and jejunum of growing rabbits. The results were consistent with the findings of Monteils et al [36] .…”
Section: Characteristics Of the Change Of Intestinal Microflora In Admentioning
confidence: 99%